PERAN TAX TREATY DAN TAX HAVEN DALAM PENGHINDARAN PAJAK INTERNASIONAL: STUDI LITERATUR ATAS REGULASI DAN IMPLIKASINYA - Loso Judijanto; Al-Amin (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyse the role of tax treaties and tax havens in international tax avoidance through a literature review of regulations and their implications. Tax treaties, which were originally designed to avoid double taxation and provide legal certainty, are often abused through treaty shopping, whereby multinational companies exploit loopholes in tax agreements to aggressively reduce their tax burden. Meanwhile, tax havens provide an environment with low tax rates, financial secrecy, and minimal requirements for substantial economic activity, thereby facilitating profit shifting and asset concealment. The symbiosis between tax treaties and tax havens amplifies the potential fiscal losses of developing countries due to tax base erosion, distorted capital allocation, and global competitive imbalances. This study highlights the importance of strengthening anti-abuse regulations, harmonising international policies, and fostering collaboration among tax authorities to mitigate the negative impacts of cross-border tax avoidance practices and ensure the sustainability of government revenue.